Cellular characteristics of keratin 19‐positive canine hepatocellular tumours explain its aggressive behaviour. Issue 1 (21st October 2017) - van Sprundel, Renee G; van den Ingh, Ted SGAM; Schotanus, Baukje A; van Wolferen, Monique E; Penning, Louis C; Rothuizen, Jan; Spee, Bart
Abstract : The expression of the hepatic progenitor cell marker keratin 19 (K19) in canine hepatocellular carcinomas is linked with a poor prognosis. To better understand this aggressive behaviour, K19‐positive hepatocellular carcinomas (n=5) and K19‐negative hepatocellular adenomas (n=6) were immunohistochemically stained for proteins involved in malignant tumour development. The K19‐positive carcinomas showed marked positivity for platelet‐derived growth factor receptor alpha polypeptide (PDGFRα), laminin, integrin beta‐1/CD29, B‐cell‐specific Moloney murine leukaemia virus Integration site 1, glypican‐3 (GPC‐3) and prominin‐1/CD133, in contrast with K19‐negative hepatocellular adenomas. Conversely, neurofibromatosis type 2 was highly expressed in the hepatocellular adenomas in contrast with the hepatocellular carcinomas. This expression pattern is clearly in line with the observed aggressive behaviour. The presence of the malignancy markers PDGFRα and GPC‐3 might make it possible to develop specific strategies to intervene in tumour growth and to devise novel serological tests and personalised treatment methods for canine hepatocellular carcinomas.